Deciphering the Dual Role of Heligmosomoides polygyrus Antigens in Macrophage Modulation and Breast Cancer Cell Growth - Patryk Firmanty; Maria Doligalska; Magdalena Krol; Bartlomiej Taciak (Veterinary Sciences, 2024)
In our study, we explored how parasitic nematodes, specifically Heligmosomoides polygyrus, influence the immune response, focusing on their potential role in tumor growth. The study aimed to understand the mechanisms by which these parasites modify immune cell activation, particularly in macrophages, and how this might create an environment conducive to tumor growth. Our methods involved analyzing the effects of H. polygyrus excretory-secretory antigens on macrophage activation and their subsequent impact on breast cancer cell lines EMT6 and 4T1. We observed that these antigens significantly increased the expression of genes associated with both pro-inflammatory and anti-inflammatory molecules, such as inducible nitric oxide synthase, TNF-α, (Tumor Necrosis Factor) Il-6 (Interleukin), and arginase. Additionally, we observed changes in the expression of macrophage surface receptors like CD11b, F4/80, and TLR4 (Toll-like receptor 4). Our findings indicate that the antigens from H. polygyrus markedly alter macrophage behavior and increase the proliferation of breast cancer cells in a laboratory setting. This study contributes to a deeper understanding of the complex interactions between parasitic infections and cancer development, highlighting the need for further research in this area to develop potential new strategies for cancer treatment.